Anti-cavitation Ni-based high-entropy alloy / ceramic composite coating and preparation method thereof

By applying Ni-based high-entropy alloy/ceramic composite coating on the surface of the turbine, the problems of abrasion and cavitation damage caused by the turbine in high heads and high sand content are solved, and the coating is high hardness, abrasion resistance and Resistant cavitation performance extends the service life of the equipment.

CN119392043AInactive Publication Date: 2025-02-07CHINA YANGTZE POWER
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411335716.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The overflow components of the turbine are severely abrasive and cavitation damaged in high watershed heads and high sand content, resulting in reduced operating efficiency, shortened safety and life.

Method used

Using Ni-based high-entropy alloy/ceramic composite coating, Ni-based high-entropy alloy powder is prepared by mixing Ni, Co, Cr, Fe and Mo, and mixed with WC powder and VC powder. The composite coating is prepared by laser cladding technology. , improve the coating's anti-wear, cavitation and impact resistance.

Benefits of technology

The coating exhibits excellent comprehensive abrasion resistance, cavitation resistance and impact resistance on the surface of the turbine, and the hardness is increased to 400-650HV0.2, the abrasion resistance reaches 3-8 times that of the substrate, and the cavitation resistance reaches the substrate. 2-5 times, extending service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an anti-cavitation Ni-based high-entropy alloy / ceramic composite coating and a preparation method, the Ni-based high-entropy alloy / ceramic composite coating is composed of 5-20 wt% of WC powder, 1-5 wt% of VC powder and 75-94 wt% of Ni-based high-entropy alloy powder, and the Ni-based high-entropy alloy powder is composed of 27-27.5 at% of Co powder, 18-19 at% of Cr powder, 12-13 at% of Fe powder, 5-10 at% of Mo powder and the balance Ni powder. According to the preparation method, the Ni-based high-entropy alloy / ceramic composite coating with excellent comprehensive abrasion, cavitation and impact resistance and high bonding strength with a matrix is prepared through the atomic ratio, the mass ratio and the laser cladding technology, the problems of abrasion, cavitation and impact on the surface of a water turbine can be solved, and the service life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high entropy alloys, and in particular relates to a cavitation-resistant Ni-based high entropy alloy / ceramic composite coating and a preparation method thereof. Background Art

[0002] In the field of hydropower generation, the abrasion damage of turbines has always been a difficult problem in the operation of hydropower stations. Under the combined effects of cavitation and sediment wear, the surface morphology of flow-through components such as turbine guide vanes and runners changes, destroying the proper flow conditions for water flow around the flow-through components, affecting the output and operating efficiency of the turbine; in addition, the material damage caused by abrasion can lead to the failure of flow-through components, and in severe cases, the unit will produce strong vibration, noise and load fluctuations, directly affecting the safety, stability and service life of the turbine. Especially in watersheds with high head and high sand content, the abrasion damage of turbines is particularly serious, and the maintenance cycle has to be shortened, and even "water is abandoned to save the machine" is forced to be used during the flood season, causing great economic losses and energy waste. Therefore, it is very urgent to solve the problems of abrasion and cavitation of flow-through components of turbines.

[0003] At present, the main measures to resist abrasion and cavitation include optimizing the design of turbine flow parts, selecting stainless steel with good abrasion and cavitation resistance as the material of flow parts, using anti-abrasion coating to protect the surface of flow parts, and reducing the sand content of water flow through sand reduction facilities. Among them, developing anti-abrasion and cavitation coating is the most economical and effective method.

[0004] At present, the most widely used anti-wear coating is hard coating, which is mainly made of metal materials, including carbides and other hard phase metal ceramics, hard wear-resistant alloys and self-fluxing alloys, etc. It has strong wear resistance and can effectively resist the wear and cavitation damage of hard particles. And with the development of high-performance surface protective coating materials and preparation technology, high-entropy alloy / ceramic composite coating prepared by laser cladding has become a new trend in the development of high-quality surface technology.

[0005] Zhang Xiaobin et al. used nickel-based self-fluxing alloy NiCrSiB powder to perform laser cladding treatment on the surface of CrNiMo stainless steel. The study found that the cladding layer had a uniform and dense structure and formed a good metallurgical bond with the substrate. At the same time, there were precipitates such as borides and boron carbides in the cladding layer, and its cavitation resistance was increased to 3 times that of the CrNiMo substrate (Zhang Xiaobin, Zang Chenfeng, Chen Suiyuan, et al. Cavitation behavior of NiCrSiB coating laser clad on CrNiMo stainless steel [J]. Journal of the Chinese Society of Nonferrous Metals, 2008, 18 (6): 1064).

[0006] CN 106400009 B discloses a low crack sensitivity and high performance Ni-based composite powder specially used for laser cladding. The raw materials and their mass percentages are as follows: 8.0-10.0% Co powder, 8.5-12.0% Fe powder, 10.0-13.0% Cr powder, 2.0-3.5% Si powder, 28.0-30.0% WC powder, and the balance Ni powder. The solid solution strengthening and fine grain strengthening mechanisms formed by the interaction of Cr, Fe, Co, Ni, and WC are used to make the cladding layer have high hardness and high toughness and low crack sensitivity. The cladding layer prepared using the powder has high surface hardness, strong corrosion resistance, and high temperature resistance. The cladding layer is prepared by a mechanical mixing method, has a simple production process, and has obvious price advantages.

[0007] However, current coatings are mainly aimed at the abrasion problem on the surface of turbines, and cavitation is the impact damage caused by the cavitation-generated air cannon on the surface of the flow-through components when it collapses, which has high requirements on the hardness and toughness of the coating. Therefore, the conventional method of increasing the hardness of the coating to resist abrasion is not suitable for the preparation of cavitation-resistant coatings. Therefore, it is necessary to provide a coating that can effectively resist cavitation to solve the more serious problem of cavitation on the surface of turbines. Summary of the invention

[0008] In view of the above technical problems, the present invention provides a cavitation-resistant Ni-based high-entropy alloy / ceramic composite coating and a preparation method thereof. Ni, Co, Cr, Fe and Mo are mixed to obtain a Ni-based high-entropy alloy powder, which is then mixed with WC powder and VC powder. A Ni-based high-entropy alloy / ceramic composite coating with excellent comprehensive anti-wear, anti-cavitation and impact resistance and high bonding strength with the substrate is prepared by laser cladding, which can solve the problems of abrasion, cavitation and impact on the surface of a turbine.

[0009] In order to achieve the above object, the present invention provides a cavitation-resistant Ni-based high entropy alloy / ceramic composite coating, which is composed of the following raw materials in atomic mass percentage: 5-20wt% WC powder, 1-5 wt% VC powder and 75-90 wt% Ni-based high entropy alloy powder.

[0010] Preferably, the Ni-based high entropy alloy powder is composed of the following raw materials in atomic percentage: Co powder 27-27.5 at%, Cr powder 18-19 at%, Fe powder 12-13 at%, Mo powder 4-5 at%, and the balance is Ni powder.

[0011] Further preferably, the particle size of the Ni powder is 30-120 μm, the particle size of the Co powder is 30-120 μm, the particle size of the Cr powder is 30-120 μm, the particle size of the Fe powder is 30-120 μm, and the particle size of the Mo powder is 30-120 μm.

[0012] Preferably, the particle size of the WC powder is 15-45 μm, and the particle size of the VC powder is 2-4 μm.

[0013] The present invention also provides a method for preparing a cavitation-resistant Ni-based high entropy alloy / ceramic composite coating, comprising the following steps: (1) Ni powder, Co powder, Cr powder, Fe powder, and Mo powder are configured according to atomic percentage to prepare Ni-based high entropy alloy powder; (2) Mechanically mixing Ni-based high entropy alloy powder with WC powder and VC powder to obtain Ni-based high entropy alloy / ceramic composite coating powder; (3) Spreading and drying the Ni-based high entropy alloy / ceramic composite coating powder; (4) Wipe the surface of the substrate clean with alcohol and dry it; (5) The dried Ni-based high entropy alloy / ceramic composite coating powder is spread on the surface of the substrate, and the cavitation-resistant Ni-based high entropy alloy / ceramic composite coating is prepared by laser cladding.

[0014] Preferably, the paving thickness in step (3) is ≤5 cm; the drying temperature is 65-85° C., and the drying time is 3-4 hours.

[0015] Preferably, the drying temperature in step (4) is 70-90° C., and the drying time is 10-20 min.

[0016] Preferably, the conditions for the laser cladding in step (5) are: a spot diameter of 4-6 mm, a laser power of 2.5-4 kW, an overlap rate of 35%-65%, a cladding head scanning speed of 7-18 mm / s, and a powder feeding rate of 20-85 g / min.

[0017] Preferably, the thickness of the cavitation-resistant Ni-based high-entropy alloy / ceramic composite coating in step (5) is 0.4-8 mm.

[0018] The beneficial effects of the present invention are: 1. Ni, Co, Cr, Fe and Mo are made into powders and mixed, and the atomic percentages of the five raw materials are increased by more than 5at% to prepare a Ni-based high-entropy alloy. By adjusting the ratio of the five raw materials, it has high hardness and high toughness, and the anti-abrasion and anti-cavitation properties of the Ni-based high-entropy alloy are synergistically improved. After being placed on the surface of a turbine to make a composite coating, it can resist the pulling force caused by water backflow, thereby avoiding the entire paint surface of the turbine from falling off and extending the service life.

[0019] 2. Mix Ni-based high-entropy alloy with WC powder and VC powder, and use laser cladding technology to make a composite coating to increase the wear resistance of the coating and prevent the coating from being eroded by sand and stones during the operation of the turbine. In addition, VC can also inhibit the growth of WC grains, while enhancing hardness and wear resistance, it can prevent sand and stone impact from impacting WC with larger grains and affecting its service life.

[0020] 3. When Ni-based high entropy alloy is mixed with WC powder and VC powder, Co and Fe can improve the bonding tightness of WC and VC, further enhance the comprehensive anti-wear, anti-cavitation and impact resistance of the composite coating, and increase the hardness to 400-650HV 0.2 The anti-abrasion performance is 3-8 times that of the substrate, and the anti-cavitation performance is 2-5 times that of the substrate. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further explained below in conjunction with specific embodiments. It is worth noting that the following embodiments are only preferred embodiments of the present invention and should not be construed as limiting the present invention. The protection scope of the present invention shall be subject to the contents recorded in the claims. Any modification or replacement made by a person skilled in the art to the technical solution of the present invention without creative work shall fall within the protection scope of the present invention.

[0022] Example 1 (1) Metal powders were prepared by gas atomization, and then various metal powders were mixed according to atomic percentage, including Ni powder: balance, Co powder: 25 at%, Cr powder: 15 at%, Fe powder: 10 at%, and Mo powder: 5 at% to prepare Ni-based high entropy alloy powder; (2) Taking each component according to mass percentage, the Ni-based high entropy alloy powder prepared in step 1: the balance, WC powder: 5wt%, VC powder: 3wt%, to prepare a Ni-based high entropy alloy / ceramic composite coating powder; (3) Lay the Ni-based high entropy alloy / ceramic composite coating powder flat, the powder stacking thickness should not exceed 5 cm, and dry it in a temperature-controlled box, where the temperature in the temperature-controlled box is 80 ° C and the drying time is 4 h; (4) Wipe the surface of 04Cr13Ni5Mo stainless steel (substrate) clean with alcohol, place it in an insulated box, and bake it at 80°C for 15 minutes to remove the oil stains on the surface and obtain a clean substrate; (5) The Ni-based high entropy alloy / ceramic composite coating powder dried in step (3) is spread on the clean substrate obtained in step (4), and a cavitation-resistant Ni-based high entropy alloy / ceramic composite coating is prepared by laser cladding; wherein the process parameters of the laser cladding are: a spot diameter of 5 mm, a laser power of 2.5 KW, an overlap rate of 35%, a cladding head scanning speed of 7 mm / s, and a powder feeding rate of 20 g / min; wherein the powder is spread to a thickness of 2 mm.

[0023] Example 2 The method and steps are the same as those of Example 1, wherein the atomic percentages of the Ni-based high entropy alloy powder in step (1) are Ni powder: balance, Co powder: 30 at%, Cr powder: 20 at%, Fe powder: 14 at%, Mo powder: 6 at%; The mass percentage of the Ni-based high entropy alloy / ceramic composite coating powder in step (2) is Ni-based high entropy alloy powder: balance, WC powder: 12 wt%, VC powder: 1 wt%; In step (5), the laser power is 3.0 KW, the scanning speed of the cladding head is 12 mm / s, and a cavitation-resistant Ni-based high-entropy alloy / ceramic composite coating is prepared.

[0024] Example 3 The method and steps are the same as those of Example 1, wherein the atomic percentages of the Ni-based high entropy alloy powder in step (1) are Ni powder: balance, Co powder: 32 at%, Cr powder: 23 at%, Fe powder: 17 at%, Mo powder: 8 at%; The mass percentage of the Ni-based high entropy alloy / ceramic composite coating powder in step (2) is Ni-based high entropy alloy powder: balance, WC powder: 15 wt %, VC powder: 1.8 wt %; In step (5), the laser power is 3.3 KW, the scanning speed of the cladding head is 12 mm / s, and a cavitation-resistant Ni-based high-entropy alloy / ceramic composite coating is prepared.

[0025] Example 4 The method and steps are the same as those of Example 1, wherein the atomic percentages of the Ni-based high entropy alloy powder in step (1) are Ni powder: balance, Co powder: 35 at%, Cr powder: 25 at%, Fe powder: 20 at%, Mo powder: 10 at%; The mass percentage of the Ni-based high entropy alloy / ceramic composite coating powder in step (2) is Ni-based high entropy alloy powder: balance, WC powder: 20wt%, VC powder: 5wt%; In step (5), the laser power is 4 kW, the overlap rate is 65%, the scanning speed of the cladding head is 18 mm / s, and the powder feeding rate is 85 g / min, thereby preparing a Ni-based high entropy alloy / ceramic composite coating that is resistant to cavitation.

[0026] Comparative Example 1 The method and steps are the same as those in Example 2, except that the atomic percentage of Co powder in step (1) is changed to 5%, and a composite coating is prepared.

[0027] Comparative Example 2 The method and steps are the same as those of Example 2, except that the atomic percentage of Co powder in step (1) is changed to 15%, and the atomic percentage of Fe powder is changed to 8%, to prepare a composite coating.

[0028] Comparative Example 3 The method and steps are the same as those of Example 2, except that the atomic percentage of Co powder in step (1) is changed to 40%, and the atomic percentage of Fe powder is changed to 23%, to prepare a composite coating.

[0029] Comparative Example 4 The method and steps are the same as those in Example 2, except that VC powder is not used in step (2) to prepare the composite coating.

[0030] Comparative Example 5 The method and steps are the same as those in Example 2, except that step (2) is omitted, and the composite coating is directly prepared.

[0031] Comparative Example 6 The method and steps are the same as those in Example 2, except that the mass percentage of WC powder in step (2) is changed to 3wt%, thereby preparing a composite coating.

[0032] Comparative Example 7 The method and steps are the same as those in Example 2, except that the mass percentage of WC powder in step (2) is changed to 25wt%, to prepare a composite coating.

[0033] The composite coatings prepared in the above embodiments and comparative examples were tested for hardness using the GB / T 4340.1-2009 "Vickers hardness test for metallic materials - Part 1: Test method", and tested for abrasion resistance and cavitation resistance using the SL / T 815-2021 "Technical Specification for Abrasion Protection of Water Pumps". The impact resistance was tested using different steel ball weights with reference to NB / T 35017-2013 "Technical Conditions for Ceramic Coated Piston Rods". The results are shown in Table 1: Table 1 Performance indicators of coatings

[0034] Note: The anti-abrasion performance and anti-cavitation performance are based on the matrix 04Cr13Ni5Mo stainless steel.

[0035] The results show that: it can be seen from Examples 1-4 that the coating has a higher hardness through the ratio of raw materials, and at the same time has higher abrasion resistance, cavitation resistance and excellent impact resistance.

Claims

1. A cavitation-resistant Ni-based high entropy alloy / ceramic composite coating, characterized in that: The invention is composed of the following raw materials in percentage by mass: 5-20 wt% of WC powder, 1-5 wt% of VC powder and 75-94 wt% of Ni-based high entropy alloy powder.

2. The cavitation-resistant Ni-based high-entropy alloy / ceramic composite coating according to claim 1, characterized in that: The Ni-based high entropy alloy powder is composed of the following raw materials in atomic percentage: Co powder 27-27.5 at%, Cr powder 18-19 at%, Fe powder 12-13 at%, Mo powder 5-10 at%, and the balance is Ni powder.

3. The cavitation-resistant Ni-based high-entropy alloy / ceramic composite coating according to claim 2, characterized in that: The particle size of the Ni powder is 30-120 μm, the particle size of the Co powder is 30-120 μm, the particle size of the Cr powder is 30-120 μm, the particle size of the Fe powder is 30-120 μm, and the particle size of the Mo powder is 30-120 μm.

4. The cavitation-resistant Ni-based high-entropy alloy / ceramic composite coating according to claim 1, characterized in that: The particle size of the WC powder is 15-45 μm, and the particle size of the VC powder is 2-4 μm.

5. A method for preparing a cavitation-resistant Ni-based high-entropy alloy / ceramic composite coating according to any one of claims 1 to 4, characterized in that: The steps include: (1) Ni powder, Co powder, Cr powder, Fe powder and Mo powder are configured according to atomic percentage and Ni-based high entropy alloy powder is prepared by gas atomization method; (2) Mechanically mixing Ni-based high entropy alloy powder with WC powder and VC powder to obtain Ni-based high entropy alloy / ceramic composite coating powder; (3) Spreading and drying the Ni-based high entropy alloy / ceramic composite coating powder; (4) Wipe the surface of the substrate clean with alcohol and dry it; (5) The dried Ni-based high entropy alloy / ceramic composite coating powder is spread on the surface of the substrate, and the cavitation-resistant Ni-based high entropy alloy / ceramic composite coating is prepared by laser cladding.

6. The preparation method according to claim 5, characterized in that: The paving thickness in step (3) is ≤5 cm; the drying temperature is 65-85° C., and the drying time is 3-4 hours.

7. The preparation method according to claim 5, characterized in that: The drying temperature in step (4) is 70-90°C and the drying time is 10-20 minutes.

8. The preparation method according to claim 5, characterized in that: The conditions for the laser cladding in step (5) are as follows: a spot diameter of 4-6 mm, a laser power of 2.5-4 kW, an overlap rate of 35%-65%, a cladding head scanning speed of 7-18 mm / s, and a powder feeding rate of 20-85 g / min.

9. The preparation method according to claim 5, characterized in that: The thickness of the cavitation-resistant Ni-based high-entropy alloy / ceramic composite coating in step (5) is 0.4-8 mm.

Citation Information

Patent Citations

  • A high-performance Ni-based composite powder with low crack sensitivity for laser cladding

    CN106400009B

  • High-entropy alloy coating layer and preparation method thereof

    CN110684978A

  • Tough wear-resistant strengthened layer and preparation method thereof

    CN113122840A

  • Ni-Co-Cr-Fe-Mo-C series anti-cavitation high-entropy alloy and preparation method thereof

    CN117626089A

  • Laser cladding high-entropy alloy coating and preparation method thereof

    CN117660957A